Mangroves Fueling Livelihoods: A Socio-Economic Stakeholder Analysis of the Charcoal and Pole Production Systems in the World’s Longest Managed Mangrove Forest - Satyanarayana, Behara; Quispe-Zuniga, Melissa R.; Hugé, Jean; Sulong, Ibrahim; Mohd-Lokman, Husain; Dahdouh-Guebas, Farid (Frontiers in Ecology and Evolution, 2021)
The declining mangrove cover worldwide highlights the necessity of understanding the linkages between ecological and socio-economic dimensions of mangrove management. This study analyses the socio-economic aspects of the pole and charcoal production systems at Matang Mangrove Forest Reserve, known as the world’s longest managed mangrove forest, in Malaysia. We performed a socio-economic survey to identify the roles and relationships among stakeholders in the pole/charcoal production system and quantified the cash-flows in monetary value. Altogether, 160 interviews were conducted with contractors, forest officials, workers, middle-men, and consumers. The contractors are functioning as a ‘hub’ from production to commercialization and receive major economic benefits. The commercialization of most charcoal (>80%) aims to its exportation to Japan while the commercialization of poles is local. Although the workers’ income was less than the minimum wage, they still prefer charcoal production jobs because of the availability and geographic proximity of these jobs. Our research suggests a standard salary and health insurance schemes for the workers to reduce social inequality/poverty and improve their well-being. Considering that mangroves occur in over 120 countries, our methodology can be used as a reference to unveil the socio-economic situation of mangrove-dependent communities as well as to map the economic cash-flow of the local activities that form the basis for long-term sustainable mangrove management plans.